Naphthodithieno[3, 2-b]thiophene-based donor-acceptor copolymers: Synthesis, characterization, and their photovoltaic and charge transport properties. (August 2016) - Zhang, Weifeng; Shi, Keli; Zhou, Weilong; Li, Zhaoguang; Chen, Zhihui; Xu, Jie; Yan, Donghang; Han, Yanchun; Wong, Man Shing; Li, Fenghong; Yu, Gui
Abstract: Herein, we report the synthesis, characterization, and their photovoltaic and field–effect properties of two dialkoxyl-substituted naphthodithieno[3, 2- b ]thiophene (NDTT )-based copolymers, namelyP1 andP2 . The NDTT-based copolymers exhibit broad absorption profiles throughout the visible spectrum up to ca. 800 nm. The copolymers have HOMO/LUMO energy levels of ca. –5.14 eV/–3.52 eV. The dialkoxyl-substituted NDTT units endow the copolymers with enhanced solution processability, and crystalline stacking thin films with small π–π distances of down to 3.59 Å. Polymer-fullerene bulk heterojunction solar cells that fabricated from a blend ofP2 /PC71 BM using diiodooctane as a solvent additive, afforded the highest power conversion efficiency of 3.54%. Solution-processed polymer field-effect transistors based onP1 with bottom-gate bottom-contact geometry exhibited promising hole mobilities of 0.070 cm 2 V −1 s −1 . Graphical abstract: Highlights: Dialkoxyl-substituted naphthodithieno [3, 2-b]thiophene (NDTT)-based copolymers were synthetized and characterized. Polymer field-effect transistors were fabricated and a high mobility up to 0.07 cm 2 V −1 s −1 was obtained. Polymer solar cells were fabricated and a power conversion efficiency of 3.54% was obtained.